Need for drug delivery systems 2 - Moreira, João Nuno (Henry Stewart Talks, 2019)
The need for delivery system in oncology, Lipid-based nanotechnologies: a clinical reality, Improving biodistribution and pharmacokinetics and safety, Improving therapeutic outcome upon increasing drug release at target organ, Targeting tumor microenvironment at two different cell levels, Improving formulation